2011
DOI: 10.1128/jb.05166-11
|View full text |Cite
|
Sign up to set email alerts
|

Interplay among Cyclic Diguanylate, HapR, and the General Stress Response Regulator (RpoS) in the Regulation of Vibrio cholerae Hemagglutinin/Protease

Abstract: Vibrio cholerae secretes the Zn-dependent metalloprotease hemagglutinin (HA)/protease (mucinase), which is encoded by hapA and displays a broad range of potential pathogenic activities. Expression of HA/protease has a stringent requirement for the quorum-sensing regulator HapR and the general stress response regulator RpoS. Here we report that the second messenger cyclic diguanylic acid (c-di-GMP) regulates the production of HA/protease in a negative manner. Overexpression of a diguanylate cyclase to increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 59 publications
(104 reference statements)
4
33
0
Order By: Relevance
“…These findings suggest that biofilm development and the general stress response are inversely regulated. Consistent with this interpretation, we found that elevated levels of intracellular c-di-GMP, a condition which favors biofilm development, diminished the expression of RpoS (22). Furthermore, we showed that the negative regulation of RpoS expression by c-di-GMP was apparently counteracted by HapR (22).…”
supporting
confidence: 76%
See 1 more Smart Citation
“…These findings suggest that biofilm development and the general stress response are inversely regulated. Consistent with this interpretation, we found that elevated levels of intracellular c-di-GMP, a condition which favors biofilm development, diminished the expression of RpoS (22). Furthermore, we showed that the negative regulation of RpoS expression by c-di-GMP was apparently counteracted by HapR (22).…”
supporting
confidence: 76%
“…At a high cell density, the quorumsensing regulator HapR inhibits biofilm formation by repressing vpsT and decreasing the c-di-GMP pool (20). In parallel, quorum sensing (HapR) positively influences the expression of rpoS (21,22). These findings suggest that biofilm development and the general stress response are inversely regulated.…”
mentioning
confidence: 72%
“…V. cholerae rpoS mutants are more sensitive to starvation, high osmolarity, and oxidative stresses, are less motile than the wild type (WT), and do not express HA/protease (35,49,58). We recently reported that RpoS diminishes the cellular concentration of c-di-GMP, an inhibitor of flagellar motility (57). Consistently, microarray studies have shown that rpoS mutants express reduced levels of multiple motility and chemotaxis genes, suggesting that rpoS could act at an early stage of the motility regulatory cascade (35).…”
mentioning
confidence: 72%
“…In V. cholerae, RpoS activates hapA and enhances the expression of motility genes belonging to the class II, III, and IV hierarchies (35,46,57). We examined the role of RpoS and H-NS in the expression of rpoN and flrA, which control the expression of the class II, III, and IV hierarchy motility genes (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation